Direct and indirect effects of alcohol expectancies through drinking motives on alcohol outcomes among students in Vietnam. (January 2016) - Diep, Pham Bich; Schelleman-Offermans, K.; Kuntsche, E.; De Vries, Nanne; Knibbe, Ronald A.
Abstract: Objective: To investigate whether the links between alcohol expectancies (tension reduction; global positive change; improved cognitive and motor abilities; and change in social behavior) and alcohol outcomes (drinking volume, 6 + drinks, alcohol problems, and symptoms of alcohol dependence) are mediated by drinking motives (social, enhancement, conformity, and coping). Method: A multi-stage sampling strategy was used in four Vietnamese provinces, resulting in a final sample of 4756 students (43.2% females) with mean age 20.6 (SD 1.8) years. Structural equation models, including indirect effects, were estimated for women and men separately. Results: Overall, there were many cases of full mediation (indirect effects range from − 0.006 to 0.083 and p -values from < 0.05 to < 0.001) and little indication of partial mediation (indirect effects range from − 0.009 to 0.025 and p -values from < 0.05 to < 0.001). In both men and women, coping motives most frequently mediated the influence of expectancies on alcohol outcomes. Among men, enhancement motives and, to a lesser extent, social motives also played a role in mediating the effects of expectancies on alcohol outcomes. Among women, full mediation was found far less often and less consistently. Conclusion: By confirming that, in Vietnam, motives mediate the link between expectancies and drinking behavior, this study supports the cultural robustness of a key assumption of the motivational model (i.e. that drinking motives are more closely associated with alcohol use than expectancies). Enhancement, coping and social motives are most frequently found as mediators among male students whereas coping motive only is most frequently found as a mediator among female students. As most of the effects of expectancies were mediated by motives, drinking motives appear to be a promising factor for interventions.